Genetic correlations and genome-wide associations of cortical structure in general population samples of 22,824 adults - Hofer, E; Roshchupkin, GV; Adams, HHH; Knol, MJ; Lin, H; Li, S; Zare, H; Ahmad, S; Armstrong, NJ; Satizabal, CL; Bernard, M; Bis, JC; et al. (Springer Nature, 2020)
Cortical thickness, surface area and volumes vary with age and cognitive function, and in neurological and psychiatric diseases. Here we report heritability, genetic correlations and genome-wide associations of these cortical measures across the whole cortex, and in 34 anatomically predefined regions. Our discovery sample comprises 22,824 individuals from 20 cohorts within the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank. We identify genetic heterogeneity between cortical measures and brain regions, and 160 genome-wide significant associations pointing to wnt/β-catenin, TGF-β and sonic hedgehog pathways. There is enrichment for genes involved in anthropometric traits, hindbrain development, vascular and neurodegenerative disease and psychiatric conditions. These data are a rich resource for studies of the biological mechanisms behind cortical development and aging.